UPAYA MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR ILMU PENGETAHUAN SOSIAL (IPS) MENGGUNAKAN MODEL PICTURE AND PICTURE PADASISWA KELAS VI SD NEGERI 1 MUTIHAN GANTIWARNO KLATEN - Papan Diyantara; Trisharsiwi Trisharsiwi (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2015)
Abstract: The objectives of this study were to describe (1) learning activities and (2) learning achievement of IPS by using picture and picture model among the sixth grade students of state elementary school 1 of Muntihan Gantiwarno Klaten. This study was a classroom action research. The data were collected by using observation, test, and documentation methods. The data quantitative from the results of observation were analyzed by using quantitative analysis by looking for the average and percentage, while the analysis of learning achievement used descriptive analysis by looking for the average and the students’ tasks. This study shows that (1) the percentage of each activity aspects increased. The average of students who did the activities in pre cycle was 10 students or 10% in fair category. In cycle 1, there were 15 students with the percentage 63% in high category, and in cycle II, there were 18 students or 77% in very high category.  (2) The average score of pre cycle was 64.78 and became 71.30 in cycle I with the success level increased 6.52%. The average of cycle II was 71.30 in cycle I and became 78.83 with the success level increased 7.53%. Based on those averages, the averages of learning activities was ≥ 70% and learning achievement of IPS was up to school standard score 70.